If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12t + 20 + 8t = 5t + -9 Reorder the terms: 20 + -12t + 8t = 5t + -9 Combine like terms: -12t + 8t = -4t 20 + -4t = 5t + -9 Reorder the terms: 20 + -4t = -9 + 5t Solving 20 + -4t = -9 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 20 + -4t + -5t = -9 + 5t + -5t Combine like terms: -4t + -5t = -9t 20 + -9t = -9 + 5t + -5t Combine like terms: 5t + -5t = 0 20 + -9t = -9 + 0 20 + -9t = -9 Add '-20' to each side of the equation. 20 + -20 + -9t = -9 + -20 Combine like terms: 20 + -20 = 0 0 + -9t = -9 + -20 -9t = -9 + -20 Combine like terms: -9 + -20 = -29 -9t = -29 Divide each side by '-9'. t = 3.222222222 Simplifying t = 3.222222222
| (5+x)(4+x)(x+3)=420 | | 27=7+37t-16t^2 | | ((5+x)(4+x)(x+3))-420=0 | | (7-i)-(8+3i)= | | 24x+30=24x+30 | | 2x-8y=-10 | | 5y-2x=-30 | | -33+58=98g-73 | | 10x-4=8x+14 | | 5x+6=55 | | 54=2x-18 | | 5x-2s+9=24 | | y-9=24 | | (3h-4)(3h-7)= | | 4(-2)+8(-2)+3(-2)+6= | | -30+6x=3x+33 | | 2x+(x-4)=2(x-3) | | p=0.1(475)+1 | | (9x+4)-(2x-8)=0 | | 10y+18=-3(5y-7)-8 | | 10x-4y+20=0 | | 15-k=20 | | 9a+6a^2=0 | | 3m(m+3)=420 | | 67.1=29.7-0.2w | | 16.1=0.1d+1 | | (3x-7)(4x-4)= | | 5+ln(x-1)=8 | | 10x=14+3x | | .42w-11=-.57w | | 14=y-2 | | 4.5x=45 |